The impact of job insecurity on long-term self-rated health - results from the prospective population-based MONICA/KORA study - Amira Barrech; Jens Baumert; Harald Gündel; Karl-Heinz Ladwig (BMC, 2018)
Abstract Background Job insecurity has been associated with impaired self-rated health (SRH) in cross-sectional studies, but prospective findings with short, medium and long-term follow-up yielded mixed findings. Therefore, the aim of the present study was to assess the long-term association between perceived job insecurity and SRH, after controlling for baseline levels of health status and life-style choices. Furthermore, three different follow-up periods (14, 19 and 24 years) were considered. Methods Data were derived from the prospective population-based MONICA/KORA cohort study (southern Germany). N = 4356 participants (2622 men and 1734 women), aged between 25 and 64 years at baseline, were included in the sample, mean follow-up was after 19.1 years. Job insecurity, SRH and risk factors were assessed at baseline during three independent surveys (1984-1995). SRH was additionally assessed in 2009. The association of job insecurity and impaired SRH at follow-up was estimated using logistic regression analyses. Results Overall, perceiving job insecurity at baseline was significantly associated with a 20% higher risk of developing impaired SRH at follow-up in the pooled analysis (OR = 1.20, 95% CI = 1.01-1.43, p = .034), even after controlling for baseline SRH, socio-demographic characteristics, lifestyle, clinical and work-related factors. The association was strongest and significant after 14 years (OR = 1.58, 95% CI 1.17-2.13, p = .003) and weaker and not significant to 19 (OR = 1.20, 95% CI 0.89-1.62, p = .24) and 24 years (OR = 0.98, 95% CI 0.73-1.32, p = .89) of follow-up in the fully adjusted models. Conclusions We found that perceived job insecurity during working life was independently and significantly associated with impaired SRH both cross-sectionally as well as after 14 years, but not after 19 and 24 years.